2019
DOI: 10.1194/jlr.ra119000274
|View full text |Cite
|
Sign up to set email alerts
|

Plasma oxyphytosterol concentrations are not associated with CVD status in Framingham Offspring Study participants

Abstract: Plasma oxyphytosterol concentrations are not associated with CVD status in Framingham Offspring Study participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…There is no clear explanation for this discrepancy, which might be caused by differences in the background diet of the study population. More recently, Fuhrmann et al [37] and Baumgartner et al [38] showed that the mean POP concentrations in two large cohorts (400‒500 subjects) were 22‒33 nmol/L, which is within the range of the data obtained in our study. These studies [37,38] further showed that none of the investigated POP, except for 7α-OH-campesterol and the 7α-OH-campesterol-to-cholesterol ratio in the Fuhrmann et al [37] study, showed an association with cardiovascular events.…”
Section: Discussionsupporting
confidence: 90%
“…There is no clear explanation for this discrepancy, which might be caused by differences in the background diet of the study population. More recently, Fuhrmann et al [37] and Baumgartner et al [38] showed that the mean POP concentrations in two large cohorts (400‒500 subjects) were 22‒33 nmol/L, which is within the range of the data obtained in our study. These studies [37,38] further showed that none of the investigated POP, except for 7α-OH-campesterol and the 7α-OH-campesterol-to-cholesterol ratio in the Fuhrmann et al [37] study, showed an association with cardiovascular events.…”
Section: Discussionsupporting
confidence: 90%
“…While some studies have shown a positive association between campesterol or absorption marker levels and cardiovascular risk, 28 , 29 , 30 others have reported conflicting results. 31 , 32 , 33 A study demonstrated that plasma campesterol was positively associated with carotid plaques in asymptomatic subjects. 28 Another study found that the combined reduction of campesterol and lathosterol predicts future cardiac events in patients with early‐stage nonischemic dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“… 30 In the Framingham Offspring Study, campesterol, sitosterol, and cholestanol were associated with coronary artery disease, while lathosterol was negatively related to the coronary disease. 31 However, contrasting results have been reported regarding the relationship between cholesterol absorption and synthesis markers and CVEs. Campesterol and sitosterol were unrelated to coronary artery disease in the EPIC‐Norfolk (European Prospective Investigation Into Cancer–Norfolk) cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…GC-MS/MS has also been scarcely utilized for the quantitative analysis of POPs. Both hydroxyl and keto forms of sitosterol and campesterol oxidation products were identified and quantified in human serum [ 67 , 68 ]. The concentrations of POPs were found to increase after consuming phytosterol-enriched food.…”
Section: Analysis Of Phytosterol Oxidation Productsmentioning
confidence: 99%